Modification of free vascularized fibular graft and its use in upper limb injuries - José Ramón Lara Espinosa; Odalys Basilia González Carrillo (Acta Médica del Centro, 2013)
The restoration with conventional osteogenic contributions is unpredictable with regard to major defects because it integrates as it consolidates their ends as a fracture. In this work, innovations in free vascularized fibular graft were made, one of the most difficult problems faced by the Orthopedics and Traumatology Specialist in the reconstruction of large segmental bone loss secondary to trauma, in congenital malformations, in osteological infections and in the bloc resection of bone tumors. The free vascularized fibular graft began to be implemented in the General Municipal Teaching Hospital Placetas in 1993, and a modification to the above mentioned technique began to be implemented in 2000; so this article will socialize the information, thus allowing the remaining specialists accessing new knowledge in the use of the technique.